2006
DOI: 10.1016/j.ydbio.2005.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Zfh1, a somatic motor neuron transcription factor, regulates axon exit from the CNS

Abstract: Motor neurons are defined by their axon projections, which exit the CNS to innervate somatic or visceral musculature, yet remarkably little is known about how motor axons are programmed to exit the CNS. Here, we describe the role of the Drosophila Zfh1 transcription factor in promoting axon exit from the CNS. Zfh1 is detected in all embryonic somatic motor neurons, glia associated with the CNS surface and motor axons, and one identified interneuron. In zfh1 mutants, ventral projecting motor axons often stall a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 56 publications
3
44
0
Order By: Relevance
“…Ectopic expression of zfh-1 leads to aberrant projections of the EW axons ( Fig. 5B and Layden et al, 2006). We have previously reported a similar mutant phenotype for eg 289 (Lundell and Hirsh, 1998), which we have shown leads to ectopic zfh-1 expression (Fig.…”
Section: The Role Of Zfh-1 In Interneuron Developmentsupporting
confidence: 72%
See 4 more Smart Citations
“…Ectopic expression of zfh-1 leads to aberrant projections of the EW axons ( Fig. 5B and Layden et al, 2006). We have previously reported a similar mutant phenotype for eg 289 (Lundell and Hirsh, 1998), which we have shown leads to ectopic zfh-1 expression (Fig.…”
Section: The Role Of Zfh-1 In Interneuron Developmentsupporting
confidence: 72%
“…These results suggest that a loss of Zfh-1 in the GW motor neuron converts it to an EW1 interneuron cell fate and that Zfh-1 is necessary for motor neuron identity in the NB 7-3 lineage. It has previously been suggested that Zfh-1 is not required for specification of cell identity in the CNS (Lai et al, 1993;Layden et al, 2006), clearly this is not the case for the GW motor neuron and there may be other undetected examples.…”
Section: Zfh-1 Is Required For the Differentiation Of Both The Gw Motmentioning
confidence: 97%
See 3 more Smart Citations